2019
DOI: 10.1155/2019/9457835
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vacuum Freeze-Drying and Vacuum Spray-Drying on Biochemical Properties and Functionalities of Myofibrillar Proteins from Silver Carp

Abstract: Fish protein powders were produced from silver carp myo brillar proteins using vacuum freeze-drying and vacuum spray-drying. Biochemical properties and functionalities of freeze-dried and spray-dried powders were determined. e myo brillar proteins were partially denatured under both the drying methods which were evidenced by the increase of free sulfhydryl content, surface hydrophobicity, and intrinsic uorescence while the decrease of the Ca 2+ -ATPase activity and percentage of the α-helical structure. With r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…These results indicated that the prolonged heat-drying process affected protein exposure to tryptophan residues and were consistent with the results of a previous study using gelatin ( Feng et al, 2021 ). Another prior study noted that the fluorescence intensity of silver carp ( Hypophthalmichthys molitrix ) myofibrillar protein increased significantly after FD and vacuum SD ( Niu et al, 2019 ). Exposure of amino acids with fluorescent properties, such as tyrosine and tryptophan, can result in an increase in fluorescence intensity ( Jiang et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicated that the prolonged heat-drying process affected protein exposure to tryptophan residues and were consistent with the results of a previous study using gelatin ( Feng et al, 2021 ). Another prior study noted that the fluorescence intensity of silver carp ( Hypophthalmichthys molitrix ) myofibrillar protein increased significantly after FD and vacuum SD ( Niu et al, 2019 ). Exposure of amino acids with fluorescent properties, such as tyrosine and tryptophan, can result in an increase in fluorescence intensity ( Jiang et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The drying process of blood can eliminate disadvantages such as spoilage ( Hou et al, 2019 ; Wang et al, 2018 ). In addition, dry form of blood powder has many commercial merits, such as low storage costs, enhancement of storage and transportation, and the ease of mixing with other materials ( Jin and Choi, 2021 ; Niu et al, 2019 ). However, depending on the drying conditions and methods, the biochemical characteristics and functional properties of the product may vary ( Lewicki, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was noteworthy that there existed remarkable differences between the surimi particles and myofibrillar proteins directly extracted from various raw materials in many aspects such as physical state, hydration capacity, conformation, emulsification, etc. [20] , [21] . However, the effects of different sequential ultrasonic processes on the physical properties and stabilization mechanisms of Pickering emulsions stabilized by surimi particles especially with low concentrations are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the content of the β-sheet is positively correlated with the α-helical content. Some studies found that the secondary structure of a protein was determined by electrostatic interactions and hydrogen bonds between amino acids ( Niu et al, 2019 ), and when the α-helical structure was denatured by heat, freezing, or oxidation, α-helical structures usually turned into β-sheet ( Guo et al, 2019 ). This result suggests that the MD group has weakened electrostatic interactions, and the stable hydrogen bonds due to heating destroyed the secondary structure of the protein and transformed the α-helical structures into β-sheet.…”
Section: Resultsmentioning
confidence: 99%